Effect of Omega-3 Polyunsaturated Fatty Acids Supplementation on Body Composition and Circulating Levels of Follistatin-Like 1 in Males With Coronary Artery Disease: A Randomized Double-Blind Clinical Trial - Shirin Jafari Salim; Shahab Alizadeh; Mahmoud Djalali; Ebrahim Nematipour; Mohammad Hassan Javanbakht (American Journal of Men's Health, 2017)
Adipokines are mediators of body composition and are involved in obesity-related complications such as cardiovascular disease. Omega-3 supplementation has not been studied in the setting of body composition and follistatin-like 1 (FSTL1) levels in patients with coronary artery disease (CAD). This study aimed to investigate the effect of omega-3 polyunsaturated fatty acid (ω-3 PUFA) supplementation on body composition indices and serum levels of FSTL1 in CAD patients. A total of 42 male (aged 45–65 years) subjects with angiographically confirmed CAD were included in this randomized, double-blind, placebo-controlled trial study. The subjects were randomly divided into omega-3 and placebo groups. During the 8-week intervention, the omega-3 group received 1,200 mg of omega-3 daily, while the placebo group received paraffin. Before and after the study, anthropometric measurements and body composition components were taken; serum FSTL1 levels were assessed by an enzyme-linked immunosorbent assay (ELISA) kit. In the omega-3 group, a significant 27.6% increase in serum FSTL1 was seen after 8 weeks of intervention ( p = .001), but no significant difference in posttreatment levels of FSTL1 was observed between the two groups ( p > .05). At the end of the study, a significant decrease in low-density lipoprotein cholesterol (LDL-C; 94.29 ± 22.04 vs. 112.24 ± 24.5; p = .01) and high-sensitivity C-reactive protein (hs-CRP; 1.92 ± 0.79 vs. 3.19 ± 2.51; p = .03) concentration was detected between the two groups. Changes in fasting blood sugar, fasting insulin, body composition, and anthropometric parameters were not significant within and between the groups. Oral omega-3 might increase FSTL1 and decrease LDL-C and hs-CRP concentrations in CAD patients. However, omega-3 supplementation did not have any effect on FSTL1 levels between the groups.